تطبيق نظام المضاربة : دراسة في بنك معاملات بماليزيا - Khalidah bt Che' Ismail; خالدة بنت جيئ إسماعيل (Universiti Sains Islam Malaysia, 2022)
The concept of Al-Mudharabah is a Islamic Muamalat system which its was recognized since on the period of Rasulullah SAW. It is the concept to separate of the profit between parties, which they were committed, the contract of investment. This research has been discuss about "The Implementation of Al-Mudharabah System: Study in Bank Muamalat Kuala Lumpur". The study sought to understand and to recognize how far the impression of the Mudharabah system to the society and also for the economic of countries. A writer was research related about this topic which the concept, proof from Al- Quran, Hadith, A1 Ijma', Hukm, condition al-Rukn and the opinion of Ulama'. Beside that's, the writer was research of the implementation Mudharabah system in Bank Muamalat, which include about the operation, objective, advantage, problem, and the impression to the society. From the result that, indicate the Islamic investment system was developed contemporary with develop economic of countries and must be improve and extend for the future.